Here are the 2 initial equations:
x^2 + y^2 = 1 x + z = 2
This is where my initial thoughts are going.
First i need to be able to express (x+z=2) in x. so we have this.
x = 2-z
next well want to sub x into (x^2+y^2=1) now we have.
(2-z)^2 + y^2 = 1
4-4z+z^2+y^2 = 1
y^2 + z^2 - 4z = -3
The above equation does not make sence to me.... Please help if you can. Is there differentation to be done somewhere along the line? I am in a coorespondace course and would really appreciate the help. Im finding it hard to understand the textbook
2006-10-29
08:54:42
·
3 answers
·
asked by
Anonymous
in
Science & Mathematics
➔ Mathematics